Using trigonometric identities, show that (cos(x) + sin(x))^2=1+sin(2x)

First being by expanding the brackets of the formula on the left:  (cos(x) + sin(x))2 = (cos(x) + sin(x))*(cos(x) + sin(x)) = cos2(x)+2cos(x)sin(x)+sin2(x).Now we must use our understanding of trigonometric identities: remember that cos2(x)+sin2(x)=1 and 2cos(x)sin(x)=sin(2x).Substituting these identities back into the expanded form of the equation, we show that (cos(x) + sin(x))2=1+sin(2x)

Related Maths A Level answers

All answers ▸

Given df/dx=2x+3 and the graph goes through (1,1), what is the function f?


Find the general solution of the differential equation: d^2x/dt^2 + 5dx/dt + 6x = 2cos(t) - sin(t)


How do you calculate the angle between two vectors?


Integral between 0 and pi/2 of cos(x)sin^2(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences